Science secrets : the truth about Darwin's finches, Einstein's wife, and other myths - Martínez, Alberto A. (University of Pittsburgh Press, 2011)
"Was Darwin really inspired by Galapagos finches? Did Einstein's wife secretly contribute to his theories? Did Franklin fly a kite in a thunderstorm? Did a falling apple lead Newton to universal gravity? Did Galileo drop objects from the Leaning Tower of Pisa? Did Einstein really believe in God? Science Secrets answers these questions and many others. It is a unique study of how myths evolve in the history of science. Some tales are partly true, others are mostly false, yet all illuminate the tension between the need to fairly describe the past and the natural desire to fill in the blanks. Energetically narrated, Science Secrets pits famous myths against extensive research from primary sources in order to accurately portray important episodes in the sciences. Alberto A. Martinez analyzes how such myths grow and rescues neglected facts that are more captivating than famous fictions. Moreover, he shows why opinions that were once secret and seemingly impossible are now scientifically compelling. The book includes new findings related to the Copernican revolution, alchemy, Pythagoras, young Einstein, and other events and figures in the history of science"--